Valuation and underpricing of Turkish IPOs - Tutuncu, Lokman (Journal of Business Economics and Management, 2020)
This study utilizes prospectuses and supplementary valuation reports to investigate the relationship between underwriters’ valuation and underpricing in 113 firms going public on Borsa Istanbul. It argues that underwriter discretion in the valuation is crucial to underpricing in the Turkish market, where fixed price is the dominant method of offering and retail investor allocation is large. Building on the overpricing theories, the study hypothesizes and finds that optimistic valuation bias is a significant determinant of underwriter discounts, and underwriter discounts are negatively associated with initial returns. One standard deviation increase in deliberate discounts is associated with a 30.4% reduction in underpricing. The median underwriter discount in the sample is 21%, while the median market-adjusted initial return is a small 1.45%, indicating that discounts might not be designed to induce underpricing and reward investors. Book-built offerings are overvalued and overdiscounted; however, not underpriced, contrasting the information extraction view.